Current state of populations, resources, and biological activity Pulsatilla patens (Ranunculaceae) in Northern Kazakhstan (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Aidarkhanova GS, Kubentayev SA, Kukhar YV, Urazalina AS. 2022. Current state of populations, resources, and biological activity Pulsatilla patens (Ranunculaceae) in Northern Kazakhstan. Biodiversitas 23: 2311-2320. Pulsatilla (Ranunculaceae Juss.) is one of the complex groups in systematic and nomenclature terms, which has more than 30 taxa. Pulsatilla species are widely used against many pathologies. Anti-inflammatory, antibacterial, antifungal, antimicrobial, antimalarial, and antitumor properties of these plants are known. The object of our research was Pulsatilla patens (L.) Mill. (Ranunculaceae) from the allopathic complex P. patens with yellow flower color in the Northern regions of Kazakhstan. The article provides detailed information on environmental and biological features, morphology, geographical distribution, phylogenetic characteristics, and raw materials of P. patens in Northern Kazakhstan. In addition to these studies, the antimicrobial and fungicidal activity of extracts from leaves and roots of the species is shown. It was established that the species grows in 6 administrative regions of Central and Northern Kazakhstan and 7 floristic regions. In the studied region, P. patens are often found along rocky foothill terraces (mainly on the southern slopes), forest edges, along the southern slopes and tops of the hills of steppes, and among shrubs. Data on the study of P. patens biomorphology showed that quantitative parameters are characterized by the greatest intra- and inter-population variability CV (number of individuals per 1 m2 (38-69%); the number of basal leaves (44-61%); the number of generative shoots per bush (32-53%). Metric parameters such as height during flowering (17-27%), height during fruiting (12-18%), flower diameter (14-24%), leaf blade diameter (11-26%) are characterized by low and medium variability, both within the population and at the inter-population level. In the phenological aspect, the species begins to grow in the first half of April. Blooms from mid-April to early May. Bears fruit from the second half of May to early June. The complete end of vegetation falls at the end of September. Analysis of biological activity of stem extracts and leaves of P. patens of Kazakhstan population showed that they have pronounced fungicidal properties in relation to conditionally pathogenic yeast Candida parapsilosis and molds Aspergillus niger. Water decoction P. patens was also active against Escherichia coli, indicating that it has antibacterial properties.
Keywords: Antimicrobial activity, fungicidal properties, medicinal plant, phytocenosis, Pulsatilla uralensis, windflower